CAMPYLOBACTER SP. IN FECES OF MARSH DEER (BLASTOCERUS DICHOTOMUS) - Giuffrida, R. [UNESP]; Modolo, J.r. [UNESP]; Araújo, J.p. [UNESP]; Duarte, J.m.b. [UNESP] (Instituto Biológico, 2024)
Campylobacter spp. was studied in feces samples from 74 marsh deer (Blastocerus dichotomus) from the western part of central Brazil, using direct growth in Butzler medium and filtration techniques. No strain species were isolated; these findings are discussed.

Campylobacter spp. foi estudado em amostras fecais de 74 cervos-do-pantanal (Blastocerus dichotomus) da região centro-oeste brasileira, utilizando técnicas de semeadura direta em meio de Butzler e técnicas e filtração. Não foram isoladas estirpes bacterianas, sendo os resultados discutidos.
CAMPYLOBACTER SPP. EM FEZES DE CERVOS DO PANTANAL (BLASTOCERUS DICHOTOMUS)
Keywords: Deer; enteropathogens; campylobacteriosis; Cervídeos; enteropatógenos; campilobacteriose